The dynamics of the MRP1/2 complex and the function of intact MRB1 core for RNA editing in Trypanosoma brucei - Huang, Zhenqiu (Jihočeská univerzita, 2015)
This thesis describes the dynamics of mitochondrial RNA-binding protein 1 and 2 (MRP1/2) complex in different cell lines of Trypanosoma brucei under an optimized immobilized condition. This study reveals the influence of RNA on the complex's dynamics. Furthermore, the function of RNA-binding complex 1 (MRB1) core has been studied via reverse genetic, biochemical and molecular techniques, with its role in RNA editing being proposed.
The dynamics of the MRP1/2 complex and the function of intact MRB1 core for RNA editing in Trypanosoma brucei
Keywords: Trypanosome; mitochondrion; organelle dynamics; FRAP; RNA editing; live cell imaging; Trypanosome; mitochondrion; organelle dynamics; FRAP; RNA editing; live cell imaging